Sistem Informasi Administrasi Surat dan Dokumentasi Kegiatan Magang Berbasis Web di PT Telkom Akses - Novanto, Ilham Setyo; Latifah, Noor (Al-DYAS, 2026)
The development of information technology has encouraged organizations to shift manual administrative processes to digital systems to improve work efficiency and accuracy. Internship administration activities at PT Telkom Akses, particularly the management of letters and documentation related to internship activities, were previously carried out manually, which could lead to process delays, data duplication, and the risk of document loss. This study aimed to design and implement a web-based Information System for Internship Letter Administration and Activity Documentation at PT Telkom Akses. The study employed a descriptive qualitative approach with a case study method, while system development was carried out using the Waterfall Model, which includes the stages of requirements analysis, system design, implementation, and testing. Data were collected through observation, semi-structured interviews, and document analysis involving administrative staff, field supervisors, and internship students. The results show that the developed system is able to integrate the management of letter administration and internship activity documentation into a single digital platform, thereby improving the efficiency of administrative processes, the accuracy of record-keeping, as well as the security and traceability of documents. Accordingly, this information system is considered effective in supporting a more structured and sustainable management of internship administration at PT Telkom Akses.